2019
DOI: 10.1038/s41598-019-46805-5
|View full text |Cite
|
Sign up to set email alerts
|

Arterial tissue transcriptional profiles associate with tissue remodeling and cardiovascular phenotype in children with end-stage kidney disease

Abstract: Chronic kidney disease (CKD) greatly increases the risk for cardiovascular disease (CVD). However, molecular mechanisms underlying CKD-induced arterial remodeling are largely unknown. We performed a systematic analysis of arterial biopsies from children with stage 5 predialysis CKD participating in the Cardiovascular Comorbidity in Children with Chronic Kidney Disease (4 C) study. For comparison, we studied biopsies from children without CKD, coronary bypass vessels from adults with atherosclerotic coronary he… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 36 publications
(47 reference statements)
0
10
0
Order By: Relevance
“…The Chronic Renal Insufficiency Cohort Study (CRIC) study found that elevated plasma levels of high-sensitivity C-reactive protein (hs-CRP) and IL-6 were associated with LVH and systolic dysfunction in CKD patients [41]. Freise et al stated that, amongst others, inflammatory processes involving tumor necrosis factor (TNF) and IL-10 impact pathobiological responses in arteries from children with CKD, and are thus associated with tissue remodeling and cardiovascular disease [42]. Furthermore, CKD patients develop endotoxemia, characterized by elevated levels of endotoxin, IL-6, CRP and lipopolysaccharide-binding protein (LBP), which contributes to chronic inflammation and has been associated with higher left-ventricular mass index (LVMI) and subsequently left-ventricular dysfunction [43].…”
Section: Inflammationmentioning
confidence: 99%
“…The Chronic Renal Insufficiency Cohort Study (CRIC) study found that elevated plasma levels of high-sensitivity C-reactive protein (hs-CRP) and IL-6 were associated with LVH and systolic dysfunction in CKD patients [41]. Freise et al stated that, amongst others, inflammatory processes involving tumor necrosis factor (TNF) and IL-10 impact pathobiological responses in arteries from children with CKD, and are thus associated with tissue remodeling and cardiovascular disease [42]. Furthermore, CKD patients develop endotoxemia, characterized by elevated levels of endotoxin, IL-6, CRP and lipopolysaccharide-binding protein (LBP), which contributes to chronic inflammation and has been associated with higher left-ventricular mass index (LVMI) and subsequently left-ventricular dysfunction [43].…”
Section: Inflammationmentioning
confidence: 99%
“…Biomineralization of tissues has been described as a common process in tissues involved in chronic vascular diseases [29,30]. Increased clinical and experimental evidence suggests that inflammation accelerates the progression of calcification, as molecules in common with bone metabolism are activated [31][32][33].…”
Section: Ivyspringmentioning
confidence: 99%
“…Increased clinical and experimental evidence suggests that inflammation accelerates the progression of calcification, as molecules in common with bone metabolism are activated [31][32][33]. Recent studies have demonstrated that RUNX2, osteopontin (OPN) and molecules involved in similar metabolic pathways play central roles in the calcification of atherosclerotic lesions and in calcification in heart disease [30,[33][34][35]. Abnormalities in the equilibrium of these proteins can cause disturbances in vascular and valvular calcification [36,37].…”
Section: Ivyspringmentioning
confidence: 99%
“…Imaging and biopsy studies have revealed increased calcium content and stiffening of arteries in early stages of CKD and in‐situ calcifications mainly in dialysis patients, but no evidence for atheroma formation 21,27,28 . Children with predialysis CKD show early changes in arterial gene transcription consistent with calcium accumulation, matrix remodelling, increased stiffness and premature ageing 28 . Thus, young patients with CKD may rapidly develop arteriosclerosis with media calcifications, while additional atherosclerotic lesions (often with intima calcifications) are seen in adult CKD patients 29 …”
Section: Lessons Learned From Children With Ckdmentioning
confidence: 99%
“…5 Earlier USRDS data for adults (1994)(1995)(1996) had shown that annual mortality from CVD was much higher in dialysis patients compared to the general population and elevated almost 1000-fold in the age group of 25-34 years. 6 A more recent similar analysis (USRDS, 2003(USRDS, -2013 in young patients with incident CKD found an incremental increase in mortality from early childhood to young adulthood (age groups 1-11, [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] and concluded that young adults with incident ESRD had a 143 to 500 times higher risk for CVD, and that CVD accounted for almost 40% of the total mortality. 7 Hence, CKD has been acknowledged as a strong and independent risk factor for CVD; patients with CKD should be considered in the highest risk group for cardiovascular events.…”
mentioning
confidence: 99%